The optimal true ileal digestible lysine requirement for nursery pigs between 27 to 44 lb - B W James; C W Hastad; K R Lawrence; J L Usry; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
A 20-d growth assay was conducted to determine the appropriate true ileal digestible lysine requirement to maximize growth performance of pigs between 27 to 44 lb. The basal diet (1.0% true ileal digestible lysine; 20.1% CP) was corn-soybean meal-based and was formulated to contain 3% added fat. Sand was substituted with L-lysineâ‹…HCl to form the other treatment diets (1.1, 1.2, 1.3, and 1.4% true ileal digestible lysine). The positive control contained more soybean meal than the basal diet (44.2 vs. 32.2% of the diet) and no L-lysineâ‹…HCl to provide 1.3% true ileal digestible lysine. Growth performance improved (quadratic, P<0.04) with increasing true ileal digestible lysine and was maximized at 1.1% true ileal digestible lysine. Feed efficiency was better (quadratic, P<0.01) for pigs fed increasing true ileal digestible lysine and was best for pigs fed 1.3% true ileal digestible lysine. These results indicate that the true ileal digestible lysine requirement for the 27 to 44 lb pig is at least 1.1% for ADG and 1.3% for feed efficiency.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Lysine; Growth performance; Nursery pigs; Swine